Influence of Citric, Acetic, and Ascorbic Acids on the Solubility of Paracetamol - Ramadhan, Dwi Sapri; Wardana, Dian; Fahmi, Jaman; Safitri, Wulan Dwi; Aulia, Amanda; purba, Gracia; Manalu, Anrian Haholongan; Damanik, Angelica; Tambunan, Ida Mariati; Zubir, Moondra; S, Abd Hakim (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
This study examined the influence of citric, acetic, and ascorbic acids on the solubility of paracetamol, an analgesic with inherently low aqueous solubility. Paracetamol tablets were dissolved in different concentrations of organic acid solutions, and dissolution times were visually monitored. The most rapid dissolution occurred in 30% acetic acid solution (190 seconds), followed by the citric–acetic acid mixture. Increasing paracetamol mass extended dissolution time, with saturation reached at 3.5 g. Enhanced solubility was attributed to hydrogen bonding interactions between organic acids and paracetamol molecules. Compared with complex techniques such as solid dispersions or co-amorphous systems, this acid-assisted approach is simple, low-cost, and requires no specialized equipment. These findings highlight the role of weak organic acids as practical solubility enhancers and suggest a promising strategy to improve paracetamol bioavailability and therapeutic effectiveness.